Cirrhosis of the liver and hepatocellular carcinoma in the outcome of chronic hepatitis C: a case report - V. V. Makashova; Kh. G. Omarova; Zh. B. Ponezheva; O. S. Astrina; V. V. Breder; I. V. Pogrebnyakov; I. A. Dzhanyan; S. A. Magomedova (Лечащий Врач, 2023)
The article presents a clinical case of cirrhosis of the liver of class C according to Child – Pugh in the outcome of chronic hepatitis C and with the development of primary liver cancer. It is shown that early diagnosis of primary liver cancer and timely initiation of antiviral therapy with a direct antiviral drug led to compensation for cirrhosis of the liver, despite the COVID-19. The course of the new coronavirus infection was complicated by hepatic cell insufficiency and encephalopathy, which required observation and treatment in the intensive care unit. Intensive therapy was carried out with the restoration of the functional state of the liver. However, the patient developed acute psychosis, and therefore he was transferred to the neurological department. The patient was discharged in a satisfactory condition with compensation for cirrhosis of the liver. Subsequently, ligation of varicose veins of the esophagus was performed, which reduced the risk of bleeding. After compensation for cirrhosis of the liver, therapy with direct antiviral drugs was prescribed. After 4 weeks from the start of antiviral therapy, HCV RNA was not detected. However, after completing the course of treatment with an ultra-sensitive polymerase chain reaction method, the hepatitis C virus was again detected, which required the extension of antiviral therapy off-label by the medical commission for another 8 weeks. Adequate antiviral therapy contributed to the cure of chronic hepatitis C, and transarterial chemoembolization of the tumor allowed to stabilize the process for the waiting stage of liver transplantation. According to the control magnetic resonance imaging, after 6 months, the stabilization of the tumor node in the liver remains, no other tumor nodes were detected. The alpha-fetoprotein level is normal. Given the continuing effect, the second course of transarterial chemoembolization is not shown. Further observation of an infectious disease specialist, oncologist continues, a consultation with a transplant specialist is recommended, control magnetic resonance imaging of abdominal organs with intravenous contrast and alpha-fetoprotein every 3 months.